Climate adaptation analysis of the main square in Kecskemét - Erdélyi, Regina; Tóth, Barnabás; Bánhidai, András; Sallay, Ágnes (4D Journal of Landscape Architecture and Garden Art, 2025)
Over the course of Kecskemét’s urban development, a densely built-up central core with low green space intensity has developed; the pedestrian square complex in the city centre therefore plays an important role in the innercity’s green space system. Kecskemét’s Main Square(Főtér) was originally formed by the reorganisation and enclosure of the historically significant market square at the junction of the commercial roads (Füzi & Walter,2005). It was pedestrianised in 1976 (Gutai, 2005) and then reconstructed in the early 2000s (Építészműhely Tervező, Beruházó és Szolgáltató Kft., 1994). With its intensively maintained and sophisticated appearance, this public space is not only a representative urban open space, but also, given its significant plant population, a key element of the green space system in terms of climate conditioning; it is bordered by wooded and paved public spaces, water architecture elements and square walls with variable architectural designs. The aim of our research was to understand the environmental and climate risks related to Kecskemét’s Main Square. For this purpose, we developed a methodology based on the collection of architectural and landscape elements that have an impact on the local climate, including human comfort.